Academic Integrity Policies of Publicly Funded Universities in Western Canada. Issue 6 (September 2022) - Stoesz, Brenda M.; Eaton, Sarah Elaine
We examined 45 academic integrity policy documents from 24 publicly-funded universities in Canada's four western provinces using a qualitative research design. We extracted data related to 5 core elements of exemplary academic integrity policy (i.e., access, detail, responsibility, approach, support). Most documents pointed to punitive approaches for academic misconduct and were based on the notion that academic misconduct results from a lack of morals. One university used the term "contract cheating, " although nearly all categorized the outsourcing of academic work as plagiarism. Details about educational resources and supports to increase student and staff understanding of academic integrity and prevention of academic misconduct were sparse. This study signals the continuing punitive nature of academic integrity policies in western Canadian universities, the reluctance to address contract cheating directly, and the need to revise policies with deeper consideration of educative approaches to academic integrity that support students and academic staff.